Consumer Brand Engagement Beyond the “Likes” - Razmus, Wiktor (Frontiers in Psychology, 2021)
In most consumer brand engagement (CBE) scales, indicators of CBE refer to behaviors that are related to social media or online brand communities. CBE also occurs beyond the Internet context in real-life settings. This paper reports the development and validation process of a CBE scale beyond the Internet behavior context. The results of three studies support the content validity, internal consistency, reliability, and nomological validity of the scale. Moreover, the results indicate that brand engagement measured by the CBE scale affects important aspects of brand-related consumer constructs. Consumers with a high level of brand engagement reflected greater brand loyalty, consumer satisfaction with a product, and perceived value of a brand. The author discusses the usefulness of this scale for marketing and psychological research.